A First Course on Time Series Analysis Examples with SAS - Falk, Michael (University of W¨urzburg, 2012)
The analysis of real data by means of statistical methods with the aid of a software package common in industry and administration usually is not an integral part of mathematics studies, but it will certainly be part of a future professional work. The practical need for an investigation of time series data is exemplified by the following plot, which displays the yearly sunspot numbers between 1749 and 1924. These data are also known as the Wolf or W¨olfer (a student of Wolf) Data. For a discussion of these data and further literature we refer to Wei (1990), Example